Pembuatan Mikroorganisme Lokal Bonggol Pisang pada Kelompok Tani Tunas Harapan Distrik Walelagama, Jayawijaya, Papua - Sumiyati Tuhuteru; Inrianti - (Institut Pertanian Bogor, 2019)
One efforts to increase crop production include improvements in cultivation systems, for examples the application of sustainable organic farming, such as use of the liquid organic fertilizers. The continuous use of liquid organic fertilizer on the soil serves to increase soil fertility. Provision of fertilizers can add nutrients to the growing media. The application of fertilizer can be in the form of organic or inorganic fertilizers. One alternative to maintain and improve crop yields is by providing liquid organic fertilizer. The purpose of this study was to provide additional knowledge related to the forms of liquid organic fertilizer and the benefits of using liquid organic fertilizer through the manufacture of Micro-Organism (MOL) banana weevil which is one form of liquid organic fertilizer that is easily obtained by the community. The activity through KKN-PPM is to provide socialization and training in making MOL of banana weevil. The result show that the community in the Walelagama District can develop knowledge related to organic fertilizers can beincrease plant productivity through the use MOL of banana weevil, whose ingredients are easily obtained so that the community can improve the existing organic farming system.